Overcoming Barriers to Family Planning through Integration: Perspectives of HIV-Positive Men in Nyanza Province, Kenya - Rachel L. Steinfeld; Sara J. Newmann; Maricianah Onono; Craig R. Cohen; Elizabeth A. Bukusi; Daniel Grossman (AIDS Research and Treatment, 2013)
This study explored barriers to and facilitators of using family planning services among HIV-positive men in Nyanza Province, Kenya. From May to June 2010, in-depth interviews were conducted with 30 men receiving care at 15 HIV clinics. The key barriers to the use of family planning included concerns about side effects of contraceptives, lack of knowledge about contraceptive methods, myths and misconceptions including fear of infertility, structural barriers such as staffing shortages at HIV clinics, and a lack of male focus in family planning methods and service delivery. The integration of family planning into HIV clinics including family planning counseling and education was cited as an important strategy to improve family planning receptivity among men. Integrating family planning into HIV services is a promising strategy to facilitate male involvement in family planning. Integration needs to be rigorously evaluated in order to measure its impact on unmet need for contraception among HIV-positive women and their partners and assure that it is implemented in a manner that engages both men and women.